The Prospects Of Islamic Microfinance: Maqasid Shariah Perspective - Hussein 'Azeemi Abdullah Thaidi; Azman Ab. Rahman; Muhamad Firdaus Ab Rahman; Muhammad Aiman Fathi Shamsuri (Institute for Research and Community Empowerment (IRCE), Tazkia University College of Islamic Economics, 2024)
Non-Indexed Publication